Effects of acetazolamide on intracranial pressure and brain tissue oxygenation on patients with acute brain injury: A pilot physiological study - Anas Hachlouf; Claudia Stella; Irene Cavalli; Elisa Gouvêa Bogossian; Sophie Schuind; Marco Anderloni; Fabio Silvio Taccone (Physiological Reports)
Abstract The effect of acetazolamide on regional brain tissue oxygenation in patients with acute brain injury (ABI) is unknown. We studied adult patients with ABI who received acetazolamide as per the treating physician's decision and had ICP and brain oxygen pressure (PbtO2) monitoring. Baseline measurements of ICP, cerebral perfusion pressure (CPP), and PbtO2 were taken before administering acetazolamide; subsequent measurements were recorded every 5 min for a total of 20 min. Mean cerebral blood velocities (FVm) and pulsatility index (PI) were measured using transcranial color‐coded duplex (TCCD) sonography at baseline and after 20 min. Fourteen patients with subarachnoid hemorrhage (n = 6), traumatic brain injury (n = 7), and intracranial hemorrhage (n = 1) were included. Following administration of acetazolamide, ICP showed a significant increase within 20 min (p < 0.001), with no significant change in CPP (p = 0.08). PbtO2 demonstrated a significant increase (p < 0.001), with a noticeable change observed at 10 min after acetazolamide administration (15 [14–17] vs. 28 [26–30] mmHg). Additionally, FVm exhibited a significant increase (p < 0.001), and PI showed a reduction (p < 0.001). Administration of acetazolamide in ABI patients resulted in a significant increase in brain oxygenation, associated with a rise in ICP and FVm, suggesting increased cerebral volume and vasodilation.